Zinc Supplementation in Children with Acute Diarrhea of Invasive Bacterial and Non-bacterial Infection - Endang Poerwati; Badriul Hegar (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2012)
Background: Diarrhea is one of the manifestations of gastrointestinal disorder. In Indonesia, diarrhea is still one of the leading causes of death in infants and children. Diarrhea requires a rational and comprehensive management to deliver an optimal result. This study was aimed to assess the effectiveness of zinc supplementation in children with acute diarrhea of invasive bacterial infection. Method: A cross-sectional study was performed in 74 children aged 2-14 years with acute diarrhea, who visited the Outpatient Clinic, Pasar Rebo Hospital Jakarta, between January and June 2011. The inclusion criteria were patients had suffered diarrhea for 1-7 days. Based on fecal analysis Results, subjects were divided into group A (non-infectious) and group B (infectious). All children received zinc supplementation. Results: The mean value of subject age was 46.6 months in group A and 81.3 months in group B. The mean frequency of diarrhea prior to zinc supplementation was 7.5 times/day in group A and 7.8 times/day in group B. Duration of diarrhea before zinc supplementation was 52.6 hours in group A and 45.4 hours in group B. On the seventh day, there was no subject of both groups who still suffered from diarrhea. Although the duration of diarrhea in group A was shorter than group B, no significant difference was found (62.4 hours vs 66.8 hours, p = 0.07). Conclusion: Zinc supplementation shows similar efficacy in children with acute diarrhea caused by invasive bacterial infection and those without bacterial infection as well. Keywords: acute diarrhea, invasive diarrhea, zinc supplementation